I-statistically pre-Cauchy double sequences - Yamanci, Ulas; Gurdal, Mehmet (Global Journal of Mathematical Analysis, 2014)
In the present paper we are concerned with I-statistically pre-Cauchy double sequences in line of of Das et al. [5]. Particularly, we prove that for double sequences, I-statistical convergence implies I-statistical pre-Cauchy condition and examine some main properties of these concepts.